2022
DOI: 10.3389/fnhum.2022.977032
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with cerebral palsy show altered responses to visual perturbations during walking

Abstract: Individuals with cerebral palsy (CP) have deficits in processing of somatosensory and proprioceptive information. To compensate for these deficits, they tend to rely on vision over proprioception in single plane upper and lower limb movements and in standing. It is not known whether this also applies to walking, an activity where the threat to balance is higher. Through this study, we used visual perturbations to understand how individuals with and without CP integrate visual input for walking balance control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The demographic characteristics of both groups are reported in our previously published work (11). The descriptive statistics for all outcome measures are presented in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The demographic characteristics of both groups are reported in our previously published work (11). The descriptive statistics for all outcome measures are presented in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Further, worsening of crouch stance was observed after removing visual input, thus indicating the dominant role visual input plays in control of standing balance in individuals with CP. With respect to walking, our recent work investigated how individuals with CP use visual input for walking balance control compared to their age-and sexmatched peers by subjecting them to visual sideways fall stimuli while walking in a virtual environment (11). Our results showed that individuals with CP had a magni ed and delayed response to visual perturbations, thus implying that they were more affected by changes in visual input and hence, relied more on vision for walking balance control.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations